Two Streptococcus agalactiae ST283 invasive infections in Portugal raise the possibility of the emergence of this unusual lineage in Europe - Martins, Elisabete R.; Forofontov, Mykyta; Mota Freitas, José; Melo-Cristino, José; Ramirez, Mário (Frontiers in Microbiology, 2026)
The importance of invasive Streptococcus agalactiae (Lancefield group B streptococci – GBS) disease among adults is increasingly recognized worldwide. Acquisition from other humans or an individual’s own microbiota is thought to be the origin of the diverse GBS lineages causing these infections. We report two cases in three consecutive years (2016–2018) of invasive GBS disease in Portugal due to the unusual ST283 lineage, a hypervirulent clone circulating in Southeast Asia (SEA) and associated to foodborne transmission and large disease outbreaks among previously healthy younger adults. The need for genetic analyses, which are infrequently performed, to identify ST283 may mean that cases of ST283 occur sporadically outside SEA but go undetected.